Redesigning the user interface of handwriting recognition system for preschool children - Aziz, Nur Sukinah; Saad, Mohd Nizam; Abd Razak, Abd Hadi; Yasin, Azman (2010)
Nowadays there are handwriting recognition systems that can be occupied to assist children learning how to write properly. However, one of the major barriers that hinders them using the system is its complex user interface where the designed is based on adult preferences. Therefore in this paper, we present the guideline to redesign the user interfaces via our experience developing a handwriting recognition system for pre-school children named Handwriting-based Learning Number (HLN). The redesign process has followed eight guidelines and rules as presented by Schniederman. The user interface satisfaction evaluation result done using Questionnaire for User Interface Satisfaction (QUIS) is very convincing where the users are almost satisfied with the redesign process that we did to the user interface. Hence we found that the guidelines are very useful and developers are all welcome to follow it if they intend to do similar system like us.